Clinical and epidemiological aspects of feline sporotrichosis caused by Sporothrix brasiliensis and in vitro antifungal susceptibility - Maschio-Lima, Taiza [UNESP]; Marques, Mariela Domiciano Ribeiro; Lemes, Thiago Henrique [UNESP]; Brizzotti-Mazuchi, Natália Seron; Caetano, Maicon Henrique [UNESP]; de Almeida, Bianca Gottardo [UNESP]; Bianco, Letícia Monteiro [UNESP]; Monteiro, Ruan Campos; Rodrigues, Anderson Messias; de Camargo, Zoilo Pires; Siqueira, João Paulo Zen; de Almeida, Margarete Teresa Gottardo (Springer Nature, 2021)
Sporotrichosis is a subcutaneous mycosis resulting from the traumatic implantation of pathogenic Sporothrix species. In Brazil, zoonotic transmission plays an important role in the epidemiology of the disease, involving especially cats. The objective of this study was to isolate Sporothrix spp. from cats with signs of sporotrichosis, determining the causative species, clinical and epidemiological aspects, and the in vitro susceptibility profile of the isolates against antifungal drugs. From September 2017 to February 2019, 245 samples of lesions were collected from symptomatic cats in São José do Rio Preto, Brazil. Identification of the isolates was performed by morphophysiological parameters and species-specific polymerase chain reaction. The susceptibility profile of the isolates was determined for five drugs (amphotericin B, itraconazole, ketoconazole, potassium iodide and terbinafine), using the broth microdilution method. Clinical and epidemiological aspects were analyzed based on data contained on investigation forms filled by the veterinarians at moment of collection. Sporothrix spp. were isolated in 189 (77.2%) of the samples. Phenotypic and molecular analyses revealed S. brasiliensis as the only causative agent. In vitro susceptibility testing showed lower MIC values for terbinafine (MIC = 0.03—2 μg/ml), ketoconazole (MIC = 0.03—2 μg/ml), and itraconazole (MIC = 0.03—4 μg/ml). Most of the animals were male (73.5%), adults (96.3%), stray (53.5%), and uncastrated (69.8%). Our results show the expansion of the S. brasiliensis epidemic to an area nearly 840 km apart from the epicenter of the long-lasting outbreak of cat-transmitted sporotrichosis in Rio de Janeiro.
Keywords: Antifungal agents; Epidemiology; Sporothrix; Sporotrichosis; Zoonoses